Non-Financial Factors Determining Employees Wellbeing in the SMEs Sector in Malaysia - Ushvanya Ravi; Shankar Chelliah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The main purpose of this study is to examine the relationship of non-financial factors that would determine SMEs sector employees’ wellbeing. An employees’ perception of and reactions to fairness in an organization, is fundamental to human psychological and social interaction. Therelationship between organizational justice (procedural justice, distributive justice, informational justice, and interpersonal justice) and wellbeing was studied to investigate the effect it has on the well-being of employees. The feeling of justice no matter promotional decision, assignment of tasks, and allocation of rewards are important to the psychological well-being of employees. The psychological and physical well-being of employees and their satisfaction with their work and workplace would affect the organizational citizenship at work, and turnover rates.